HUBUNGAN PERENCANAAN MANAJEMEN STRATEGIS DAN BUDAYA ORGANISASI TERHADAP KEPATUHAN TENAGA KESEHATAN DALAM PROGRAM PENGENDALIAN RESISTENSI ANTIMIKROBA DI RSUD SAYANG CIANJUR - Lisa Rahmah Agustini; Arif Rachman; Budi Santoso (Journal of Innovation Research and Knowledge, 2025)
Antimicrobial resistance is one of the major challenges in modern healthcare that requires strong managerial attention and a supportive organizational culture. This study aims to analyze the influence of strategic management planning and organizational culture on healthcare workers’ compliance in the implementation of the Antimicrobial Resistance Control Program (PPRA) at RSUD Sayang Cianjur. This research employed a quantitative approach with a descriptive correlational design. A total of 100 respondents were selected using purposive sampling. Data were collected through a closed-ended Likert-scale questionnaire and analyzed using multiple linear regression with SPSS. The results indicate that strategic management planning has a positive and significant influence on healthcare workers’ compliance. Similarly, organizational culture also shows a positive and significant influence. Simultaneously, both variables explain 83.2% of the variance in healthcare workers’ compliance. These findings highlight the importance of synergy between managerial approaches and the development of organizational culture in supporting the successful implementation of the PPRA. This study contributes both theoretically and practically to hospital management in designing system-based interventions supported by a strong and professional work culture